Association of center-level operative volume and acute outcomes following robotic-assisted colectomy for colorectal cancer. - Nam Yong Cho; Shineui Kim; Joseph Hadaya; Nikhil Chervu; Shayan Ebrahimian; Emma Cruz; Hanjoo Lee; Peyman Benharash (PLoS ONE)
Background The adoption of robotic-assisted colectomy (RAC) remains limited due to high costs. There is a paucity of data regarding the impact of institutional robotic experience on costs in patients undergoing RAC for colorectal cancer. Methods All adult patients undergoing RAC for colorectal cancer were identified using the 2016-2020 Nationwide Readmissions Database. A multivariable regression to model major adverse events (MAE) was developed with the inclusion of institutional robotic surgery volume as restricted cubic splines. The volume corresponding to the inflection point of the spline was used to stratify hospitals into high- (HVH) or low-volume (LVH). We subsequently examined the association of HVH status with costs, length of stay (LOS), MAE, non-home discharge and 30-day unplanned readmission. Results Among the 39,064 patients undergoing RAC, 65.2% were treated at HVH. Following risk adjustment, RAC at HVH was associated with reduced index hospitalization costs by $2,000 (95%CI $1,500-2,400) and LOS by 0.3 days (95%CI 0.2-0.5 days) as well as decreased odds of MAE (AOR 0.86, 95%CI 0.77-0.96). Both non-home discharge and 30-day unplanned readmission were not associated with hospital volume. In our cross-volume analysis, we found an increase in institutional RAC and overall robotic volumes to be associated with reduced odds of MAE. Conclusion The present study demonstrated higher institutional robotic-assisted operation volume to be associated with reduced MAE and cost in patients undergoing RAC. The findings suggest the potential benefits of increasing expertise and implementing efficient practices in robotic-assisted surgery programs.